Mastering Ejaculation Challenges Through Comprehensive Strategies: A Case Report - Poudel , Binod; Baral, Kamal Raj (Journal of College of Medical Sciences-Nepal, 2024)
Background This case report explores the successful management of psychogenic anejaculation in a 31-year-old poultry farmer. Despite an 8-year history of anejaculation during intercourse, the patient achieved ejaculation during masturbation. Initial pharmacological intervention with duloxetine, a selective serotonin and norepinephrine reuptake inhibitor, provided partial success. To address persisting challenges, dual sex therapy and sensate focus therapy were introduced, based on the work of Masters and Johnson. The integrated approach proved effective, leading to successful ejaculation and the conception of the patient's wife. This case emphasizes the necessity of a comprehensive approach to psychological anejaculation, combining pharmacological and psychotherapeutic interventions for successful outcomes.